Beyond theodicy : Jewish and Christian continental thinkers respond to the Holocaust - Pinnock, Sarah Katherine (SUNY series in theology and continental thought., 2002)
"Beyond Theodicy analyzes the rising tide of objections to explanations and justifications for why God permits evil and suffering in the world. In response to the Holocaust, striking parallels have emerged between major Jewish and Christian thinkers centering on practical faith approaches that offer meaning within suffering. Author Sarah K. Pinnock focuses on Jewish thinkers Martin Buber and Ernst Bloch and Christian thinkers Gabriel Marcel and Johann Baptist Metz to present two diverse rejections of theodicy, one existential, represented by Buber and Marcel, and one political, represented by Bloch and Metz. Pinnock interweaves the disciplines of philosophy of religion, post-Holocaust thought, and liberation theology to formulate a dynamic vision of religious hope and resistance."--Jacket